Normative Construction and Practical Implications of Industrial Design Disputes: A Juridical Analysis of the Geprek Bensu Case - Adi Permadi; Faris Makarim Pranotoputera; Asep Husni; Muhammad Athaillah Shahibul Hikam; Tatang Astarudin (Fakultas Syariah IAIN Langsa, 2026)
Ideally, legal protection for industrial designs in Indonesia consistently adheres to the first-to-file principle, in which the party who first registers their design lawfully and in good faith is entitled to exclusive legal protection. However, in reality, complex disputes arise—as seen in the Geprek Bensu case—where claims over design ownership involve interpretations that touch upon morality, business reputation, and the applicant’s intent. This study aims to analyze the normative construction and practical implications of court decisions in the industrial design dispute between PT Ayam Geprek Benny Sujono and Ruben Onsu, with an emphasis on how the first-to-file principle is applied and interpreted in Indonesian legal practice. The method used in this research is normative legal research with a qualitative-descriptive approach, based on library research of relevant laws, court rulings, and legal literature. The findings indicate that, from a juridical perspective, the Supreme Court firmly upheld the first-to-file principle as stipulated in Article 12 of Law No. 31 of 2000, and rejected claims submitted without novelty and good faith. Normatively, the ruling forms a legal construction that clarifies the standards for industrial design registration and has practical implications by encouraging business actors, particularly MSMEs, to be more proactive in registering their designs lawfully and with integrity to obtain strong legal protection.